Evalution et diversite du concept d'amenagement forestier - Bertrand, A.; Babin, D.; Nasi, Robert (1999)
Management means allocating and distributing limited resources to achieve clearly defined targets. This definition helps towards a clear summary of the way ideas to do with forest management have been developing. Areas of concern have been gradually shifting form technical assignments (resource allocation and distribution) towards the issue of defining management goals (who? how?). This development leads from sustained timber production to the sustainable management of forest ecosystems against a backdrop of land planning. considering the many people involved in forest management, and their concerns, which all carry the same kind of weight, it is necessary to single out the problem of decision-making procedures. Management must reconcile differing, not to say contradictory, goals in one and the same area. Managing a forest thus means, first and foremost, a successful negociation